Buddhism and healing in the modern world - Salguero, C. Pierce; Cheung, Kin; Deane, Susannah (University of Hawai'i Press, 2024)
"This rich collection focuses on the nexus between Buddhism and healing in the modern and contemporary world, highlighting the many ways Buddhists have adapted in response to and in dialogue with modern science, biomedicine, and other facets of modernity from the nineteenth century to today. Buddhist healing activities are much more diverse than the narrow range of mindfulness techniques that have dominated scholarly and popular focus. From the community-based healing practices of Asian American Buddhists and transnational Tantric sex therapy retreats to concerns about balancing being contemporary with being authentically Buddhist, contributors explore how Buddhists have rethought the mind-body relationship against the backdrop of the modernization and globalization of Buddhism. They examine Buddhists navigating the differences and commonalities that exist in their practice and modern systems of mental and physical healthcare, paying attention to how they have negotiated shifting configurations of legitimacy, authority, and authenticity. Through historical and ethnographic case studies, the work details these ruptures and reconciliations in Japan, Sri Lanka, Tibet, Korea, and the U.S., in addition to mapping the transnational pathways of exchange as knowledge about Buddhism and medicine has traveled between Asia and the West. Buddhism and Healing in the Modern World encompasses a wide range of Buddhist ideas about health and health-seeking practices that remain a vital part of the everyday practice of modern Buddhism across the globe"--